Sono e funcionalidade familiar: um estudo com idosos cuidadores - Ferreira, Isabela Bonifácio de Almeida (Universidade Federal de São Carlos, 2021)
In the Brazilian context, older people care is culturally handled by a family member. Given the recent new family arrangements and the aging of the population, the number of older adults taking care of other older people is increasing. However, the responsibility of care can arise suddenly, and the family caregiver is not always able to assume this responsibility. In this case, the family members may not organize themselves, resulting in conflicts, disharmony, and consequent family dysfunction. Researchers claim that a dysfunctional context can have a negative impact on individuals’ physical health and, consequently, the caregivers' sleep may be negatively affected. Therefore, both family dysfunction and sleep issues among caregivers can interfere in the quality of the provided care, especially in contexts of poverty. Objective: analyzing the relationship between sleep and family functionality of older caregivers registered in Family Health Units in a context of high social vulnerability. Method: cross-sectional study, based on quantitative research assumptions, carried out in a countryside city in the state of São Paulo - BR. This is an excerpt from a larger study, in which 65 older adults aged 60 years or older participated, registered and residing in the urban area covered by the Family Health Units and who take care of other older adult. Data collection was performed in the older adult houses, in a place provided by the family from July/2019 to March/2020. The following instruments were used for the individual interviews: Questionnaire to characterize both the elderly caregiver and the care context, Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and Family APGAR to assess family functionality. Divergencies between groups were analyzed using Pearson’s Chi-Squared and Fisher's exact tests. The significance level adopted for the statistical tests was 5%. Results: most of the older caregivers were female, with a mean age of 69.1 (6.4) years, married, caring for their partner, without previous training or help from third parties with the responsibility of caring. Regarding the sleep quality, 50.8% of older caregivers reported poor sleep. In relation to family functionality, 66.2% of older caregivers had good family functionality, 16.9% had moderate dysfunction and 16.9% had high family dysfunction. There was no statistically significant relationship between the total scores of the sleep instruments and family functionality. There was only statistical significance between family functionality and other sleep disorders caused by preoccupation (p=0.019). Conclusion: There was a higher rate of family dysfunction among older caregivers who had sleep disorders due to a very frequent preoccupation when compared to others.
Sleep and family functioning: a study with older caregivers
Keywords: Cuidadores; Idoso; Relações familiares; Sono; Enfermagem geriátrica; Caregivers; Aged; Family relations; Sleep; Geriatric nursing; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA